Agonistic Autoantibodies to the β2-Adrenergic Receptor Involved in the Pathogenesis of Open-Angle Glaucoma - Jünemann, Anselm; Hohberger, Bettina; Rech, Jürgen; Sheriff, Ahmed; Fu, Qin; Schlötzer-Schrehardt, Ursula; Voll, Reinhard Edmund; Bartel, Sabine; Kalbacher, Hubert; Hoebeke, Johan; Rejdak, Robert; Horn, Folkert; et al. (Frontiers in Immunology, 2018)
Glaucoma is a frequent ocular disease that may lead to blindness. Primary open-angle glaucoma (POAG) and ocular hypertension (OHT) are common diseases with increased intraocular pressure, which are mainly responsible for these disorders. Their pathogenesis is widely unknown. We screened the sera of patients with POAG and OHT for the prevalence of autoantibodies (AAb) against G protein coupled receptors (GPCRs) in comparison to controls. Employing frequency modulation of spontaneously contracting neonatal rat cardiomyocytes in vitro, agonistic GPCR AAb were to be detected in roughly 75% of the patients with POAG and OHT, however not in controls. Using inhibitory peptides the AAb’ target was identified as ß2 adrenergic receptor (ß2AR). The AAb interact with the second extracellular loop of ß2AR. The peptides 181-187 and 186-192 were identified as binding sites of the AAb within the extracellular loop II. The binding of the AAb to ß2ARs was verified by surface-plasmon-resonance analysis. The isotype of the AAb was (immunoglobulin) IgG3. In an additional pilot principal-of-proof study including 4 patients with POAG, the removal of the AAb against the ß2AR and other immunoglobulins G by immunoadsorption resulted in a transient reduction of intraocular pressure. These findings might indicate a possible role of agonistic AAb directed against ß2ARs in the dynamics of aqueous humor and might support a contribution of adaptive autoimmunity in the etiopathogenesis of POAG and OHT.